Decision-Making Participation Patterns: The Role of Organizational Context - Connor, Patrick E. (Academy of Management Journal, 1992)
Patterns of employees' participation in a number of specific decisions were studied in 101 Oregon nursing homes. The inquiry concerned whether such patterns vary according to the contextual properties of facility size, skill level, and profit-making orientation. Although interaction effects varied, main-effect results were strong.